Effects of Janus kinase inhibitor tofacitinib on circulating serum amyloid A and interleukin‐6 during treatment for rheumatoid arthritis. (February 2014) - Migita, K.; Izumi, Y.; Jiuchi, Y.; Kozuru, H.; Kawahara, C.; Izumi, M.; Sakai, T.; Nakamura, M.; Motokawa, S.; Nakamura, T.; Kawakami, A.
Summary The Janus kinase inhibitor tofacitinib is currently being investigated as a disease‐modifying agent in rheumatoid arthritis (RA). We investigated the in‐vivo effects of tofacitinib treatment for 4 weeks on elevated circulating acute‐phase serum amyloid (SAA) levels in 14 Japanese patients with RA. SAA levels fell from 110·5 ± 118·5 μg/ml (mean ± standard deviation) at treatment initiation to 15·3 ± 13·3 μg/ml after 4 weeks treatment with tofacitinib. The reduction in SAA levels was greater in patients receiving tofacitinib plus methotrexate compared with those receiving tofacitinib monotherapy. Tofacitinib was also associated with reduced serum interleukin (IL)‐6, but had no effect on serum levels of soluble IL‐6 receptor. Patients were divided into groups with adequate (normalization) and inadequate SAA responses (without normalization). Serum IL‐6 levels were reduced more in the group with adequate SAA response compared with those with inadequate SAA response. These results suggest that tofacitinib down‐regulates the proinflammatory cytokine, IL‐6, accompanied by reduced serum SAA levels in patients with active RA. The ability to regulate elevated serum IL‐6 and SAA levels may explain the anti‐inflammatory activity of tofacitinib.